21a+14b-c=0

Simple and best practice solution for 21a+14b-c=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21a+14b-c=0 equation:


Simplifying
21a + 14b + -1c = 0

Solving
21a + 14b + -1c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-14b' to each side of the equation.
21a + 14b + -14b + -1c = 0 + -14b

Combine like terms: 14b + -14b = 0
21a + 0 + -1c = 0 + -14b
21a + -1c = 0 + -14b
Remove the zero:
21a + -1c = -14b

Add 'c' to each side of the equation.
21a + -1c + c = -14b + c

Combine like terms: -1c + c = 0
21a + 0 = -14b + c
21a = -14b + c

Divide each side by '21'.
a = -0.6666666667b + 0.04761904762c

Simplifying
a = -0.6666666667b + 0.04761904762c

See similar equations:

| 4(3-6x)-6(x-2)=-66 | | 93(6*4/8) | | 15=9-3(b-11) | | 5+4(-3-4m)=121 | | -2(2+a)=2 | | 4(3-6x)-6(x-2)=66 | | 8x^2-4xy=0 | | 50=-3s-2s | | 600+2000x=7500 | | 61n-12=4j | | 4(6+s)=24 | | 2a+3whena=8 | | 1.2x-6y=12 | | 17x+10=8x | | 32=r+7r | | -17+17f=3+18f | | (2x+4)+(3x+1)=x | | -5x+7y=-36 | | Y-2=3/5(x-5) | | 3a+12b+1c=15 | | (4x-7)+(8x+10)= | | 12x-2(5x-3)=46 | | (5/6c)-(3/4)=(11/12) | | 2(5+2x)+4=26 | | -4x+3=x+18u | | 24b^3-18b^2=0 | | 3(x+3)+2=17 | | 15x+2=28 | | V=S*(P*0.018+0.5) | | x+0.46x= | | 5(-2x-9)+12(4+x)=18 | | (mn)-3= |

Equations solver categories